Approximation algorithms for demand-based job scheduling with reconfigurable resources - Bergé, Pierre; Chaikovskaia, Mari; Gayon, Jean Philippe; Quilliot, Alain (Discrete Applied Mathematics, 2026)
We consider a scheduling problem with reconfigurable resources. Several types of jobs (e.g. transportation tasks, production operations) have to be processed by a set of identical resources (e.g. robots, workers, processors) over a discrete time horizon. In each time period, teams of resources must be formed to process jobs. During a given time period, a team handles one type of job and the number of jobs that can be processed depends on the team size. A resource which is used to perform some job type in a given period may be employed for another job type in the next period. The objective is to determine the minimum number of resources needed to meet a given demand for each job type. We show that the resulting strongly NP-hard Multi_Bot problem may be handled in a greedy way with an approximation ratio of 4/3. Furthermore, as a more general and theoretical statement, we present a PTAS for Multi_Bot. •Properties of the MultiBot problem and relationship with other problems.•Approximation algorithm with constant factor 4/3.•Polynomial-time approximation scheme for Multibot.